How to Measure the Unobservable: A Panel Technique for the Analysis of TFP Convergence - Adriana Di Liberto; Roberto Mura; Francesco Pigliaru (Fondazione Eni Enrico Mattei (FEEM), 2005)
This paper proposes a fixed-effect panel methodology that enables us to simultaneously take into account both TFP convergence and the traditional neoclassical-type of convergence. We analyse a sample of Italian regions between 1963 and 1993 and find strong evidence that both mechanisms were at work during the process of aggregate regional convergence observed in Italy up to the mid-seventies. Finally, we find that our TFP estimates are highly positively correlated with standard human capital measures, where the latter is not statistically significant in growth regressions. This evidence confirms one of the hypotheses of the Nelson and Phelps approach, namely that human capital is the main determinant of technological catch-up. Our results are robust to the use of different estimation procedures such as simple LSDV, Kiviet-corrected LSDV, and GMM à la Arellano and Bond.
Keywords: O47; O33; O18; C23; 330; TFP; Panel data; Regional convergence